Development of energy flow models to predict sound fields for sound absorbing structures in medium-to-high frequency ranges. (March 2021) - Kim, Tae-Gyoung; Hong, Suk-Yoon; Song, Jee-Hun; Kwon, Hyun-Wung
Energy flow analysis (EFA) model for the treatment of sound absorbing structures is developed to predict sound fields of engineering systems in medium-to-high frequency ranges. Thus far, EFA for acoustic models has been developed only for low damping media, such as air and water. A new energy flow governing equation is derived in this study by identifying a relationship between energy density gradient and intensity and acoustic energy dissipation for sound absorbing materials. With the developed EFA model, dispersive wave, and loss factors are identified using complex acoustic properties, and they are investigated to make ensure that they reflect the properties of sound absorbing materials. By solving the governing equation, acoustic energy density, and intensity distributions in sound absorbing materials are obtained, and noise analyses are performed for sound absorbing structures. They are compared with those obtained via a conventional method and experimental result for the verification, in which we confirmed that both results agreed well. Furthermore, various sound absorbing structures are analyzed using the developed EFA model to predict sound fields in medium-to-high frequency ranges. It is demonstrated that the developed EFA model is useful for medium-to-high frequency ranges.